Language Learning beyond English - Lanvers, Ursula (Cambridge University Press, 2025)
This Element concerns language learning in the age of Global English. Learning just English fails to achieve the desired results. It proposes a new matrix of rationales for language learning, advocating an interconnected, socially embedded justification for language learning. This title is also available as Open Access on Cambridge Core.